Effectiveness of Decoction of Cinnamon Bark (Cinnamomum Burmanii) as A Fly Repellant In The Drying Process of Salted Fish - Syahrurradi, Muhammad; Zubaidah, Tien; Irfa'i, Muhammad; Pahruddin, Muhammad (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Flies are vectors that can transmit disease to humans. Therefore, it needs to be controlled. To control flies, use natural insecticides (natural repellents). This study aimed to determine the effectiveness of the decoction of cinnamon bark (Cinnamomum burmanii) as a fly repellent in the drying process of salted seat fish. This type of study is quasi-experimental, with a posttest-only control group design. The samples in this study were flies found in the wild. It consisted of 5 treatments, one control, and four repetitions (replications). The ANOVA test showed that varying doses of boiled cinnamon bark (Cinnamomum burmanii) as a fly repellent affected drying salted fish. The sig value is 0.00 < 0.05. The difference in the repellent power of the 12% dose was 14.47%, the 15% dose was 37.35%, the 18% dose was 55.2%, the 21% dose was 67.71%, and the 24% dose was 83.63%. It is hoped that the public can use a decoction of cinnamon bark as a natural repellent for fly vectors.